PENDIDIKAN KARAKTER DALAM KELUARGA: STUDI ATAS HADIS PENDIDIKAN KARAKTER DALAM KELUARGA - Lutfiyani Lutfiyani; Ahmad Suhendra (ISSUE: Journal of Islamic Studies for Universal Dialogue, 2023)
AbstractCharacter education in the family is very important for a child’s development. Education is a means to educate the nation in order toelevate the human. Readings traditions character education in the family in its various aspects is very important. Thus, this article willexamine the character education from the perspective of tradition. Hadith character education issued by Ibnu Majah no. 3661 indicating the existence of two principles that can be taken, which glorify or loved children (akrimū awlādakum) and educate the child character (aḥsinū adābahum).